ANALYSIS OF DEXAMETHASONE AND PARACETAMOL CONTENT IN HERBAL MEDICINES FOR MUSCLE PAIN IN TERNATE CITY USING UV-VIS SPECTROPHOTOMETRY - Dessy Trisiani; Maghfira Maulani; Abulkhair Abdullah; Muh. Nasir (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Jamu Pegal Linu (herbal medicines for muscle pain) is one of the most commonly consumed traditional herbal drinks to relieve muscle soreness and pain caused by fatigue. The high demand for jamu has led to some irresponsible producers adding Active Pharmaceutical Ingredient (API). The APIs commonly found are paracetamol and dexamethasone. This is a violation of the Indonesian Ministry of Health Regulation Number 007 of 2012 concerning Traditional Medicine Registration, which states that traditional medicine must not contain pharmaceutical chemicals. To detect the presence of paracetamol and dexamethasone in jamu pegal linu in Ternate City, 10 samples were analyzed qualitatively using Thin Layer Chromatography (TLC) with a mobile phase of chloroform:methanol (9:1), and quantitatively using validated UV-Vis spectrophotometry methods, including linearity, precision, accuracy, LOD, LOQ, and determination of content. Based on TLC testing, 5 samples were suspected to contain paracetamol, and 3 were suspected to contain dexamethasone. The validation results showed that all parameters met the requirements: R² ≥ 0.99, recovery 85.289–92.541%, RSD ≤ 0.79%, LOD 0.204–0.336 µg/mL. Based on qualitative analysis using TLC and quantitative analysis using UV–Visible spectrophotometry, several jamu pegal linu products sold in Ternate City were found to contain active pharmaceutical ingredients. Of the ten samples analyzed, 30% were suspected to contain dexamethasone and 50% were suspected to contain paracetamol. These findings indicate a significant presence of pharmaceutical adulterants in herbal medicines marketed in Ternate City. However, confirmatory analysis using more specific techniques such as High Performance Liquid Chromatography (HPLC) or Liquid Chromatography–Mass Spectrometry (LC-MS) is recommended to strengthen the validity of the results.